Pelayanan Jasa Service Komputer Dalam Meningkatkan Loyalitas Pelanggan Recovery.U - Annisya Sekar Cakra Buana; Mukjizah Dwi Prihartina; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Computer service providers need to pay attention to the needs and expectations of customers to retain and attract new customers. Companies also need to invest in employee training and development, improving operational processes, and improving service efficiency. Quality computer service services have a very important role in increasing customer loyalty. The purpose of this industrial visit is to provide direct experience and insight to understand directly how the computer service process is carried out and can provide an opportunity to see firsthand how computer technicians carry out their duties. The author uses a descriptive method with an observative. Primary data obtained is through interviews and direct observation of business actors and secondary data obtained from articles or books related to the title of writing. Based on the industrial visit, the authors obtained the results that the Recovery.U company prioritizes service both technically and provides responsive suggestions and input in handling customer requests to increase customer loyalty. Quality and satisfaction affect customer loyalty. Creating customer satisfaction with good service quality has benefits such as providing a good basis for repeat use of services by customers because it creates customer satisfaction and loyalty. To be able to improve the company's services, it is necessary to increase the number of employees needed based on the volume of work, the level of customer demand, and the scope of services offered so that in the future it can receive more customer requests every day due to the appropriate employee capacity.